Enhanced biohydrogen production from the dark co-fermentation of tequila vinasse and nixtamalization wastewater: Novel insights into ecological regulation by pH. (1st October 2019) - García-Depraect, Octavio; Rene, Eldon R.; Gómez-Romero, Jacob; López-López, Alberto; León-Becerril, Elizabeth
Graphical abstract: Highlights: The pH effect on the ecology of lactate-based dark fermentation was studied. pH control was crucial to shorten the lag time and reduce propionogenesis. Key microbial structure for enhanced bioH2 production was driven by pH modulation. BioH2 production from lactate relied on the functional organization of the bacteria. BioH2 production: 2.5 NL/L of reactor and 3.7 NL/L-d were achieved in this study. Abstract: The main aim of this work was to study the effect of pH on lactate- and acetate-based bioH2 production from the dark co-fermentation of 80% tequila vinasse and 20% nixtamalization wastewater ( w/w ) by mixed culture. A 3-L well-mixed batch reactor was operated at constant pH values of 5.8 and 6.5, with an accuracy of ±0.05 pH units in all the cases. Regardless of pH, bioH2 production derived mostly from the consumption of lactate. No significant differences were observed in the amount of bioH2 produced, i.e. 2133 NmL/Lreactor with a maximum rate of 155 NmL/L-h. Compared to a pH of 5.8, pH 6.5 shortened the lag time but promoted bioH2 sink through propionate formation. Based on the above results, a two-stage controlled-pH strategy was proposed by maintaining the first stage at pH 6.5 and the second stage at pH 5.8 for avoiding long fermentation time and propionogenesis, respectively. The pH-shift strategy reduced the operational time and enhanced bioH2 production by 17%. Besides, this strategy also stimulated the syntrophy between Clostridium and Lactobacillus, and reduced the proliferation of Blautia and Propionibacterium, trending bioH2 production to enhanced efficiency. Overall, microbial dynamics showed that successful bioH2 production from lactate and acetate relies on having an optimum microbial equilibrium between producers and consumers of lactate and acetate, which was found to be pH-dependent.